Detection of Fatty Acids Separated from Melissa Officinalis Leaves Using GLC Technology and Studying their Effect on the Vitality of Staphylococcus Aureus - Mahmoud, Qahtan Khalaf; Mikhlif, Rafee Zaidan; Hasan, Hasan Mohammed (Newinera Publisher, 2022)
The plant found in Mosul exhibited distinct characteristics in terms of its composition of Undecanoic acid and Linoleic acid. Notably, the highest concentration of fatty acids was observed in the leaves of the plant cultivated in the Aqrah district, measuring 9.908 mg/g. The findings of the present study demonstrate that fatty acids exhibit antioxidant properties against the free radical DPPH. Moreover, it was observed that the efficacy of these fatty acids in neutralizing the free radical increases proportionally with the concentration of the active compounds. At a concentration of 500 μg/ml, the fatty acids (Mosul) exhibited the highest level of inhibition, with a rate of 86.4%. This inhibition rate was found to be superior to that of fatty acids (Aqrah) at the same concentration, which showed an inhibition rate of 79.25%. Furthermore, the observed inhibition rate of fatty acids (Mosul) was statistically significant and comparable to the standard sample of ascorbic acid at the same concentration, which exhibited an inhibition rate of 85.6%. Following these results, the concentration of fatty acids (Mosul) is 400 micrograms per milliliter, exhibiting an inhibition rate of 81.2%. In comparison, fatty acids (Aqrah) achieved an inhibition rate of 72.3% at the same concentration. Other concentrations displayed varying degrees of inhibition capacity towards DPPH free radicals. The study provided confirmation of the inhibitory effects of fatty acids on the viability of Staphylococcus aureus strains isolated from infected individuals at Tikrit Teaching Hospital.